Normal Pituitary Gland Size and Morphology and Its Variations Related To Age and Gender: An MRI Evaluation - Jha, Amit; Paudel, Nabin; Nepal, Sabin; Nayak, Rajesh (Journal of Nepalgunj Medical College, 2020)
Introduction: The pituitary gland is regarded as the master endocrine gland of the body. Subtle alterations in the size can cause significant changes to other endocrine glands and hormonal status. Magnetic Resonance Imaging (MRI) is the investigation of choice to examine pituitary gland. It is important to know the range of normal size and variations according to age and gender to enable radiologists to suggest what might be an abnormal pituitary gland. Aims: This study aims to examine normal size, volume and shape of pituitary gland and to establish a normal reference value for pituitary size in different age groups and genders. Methods: MRI Brain of 137 patients were studied retrospectively and patients with endocrinal abnormalities were excluded from the study. Images were acquired in General Electronics 1.5 Tesla MRI machine and mid-sagittal T1WI and coronal T2WI were selected for accurate measurement of the gland. Height, AP diameter, Transverse diameter, and volume were calculated for each individual and the collected data was categorized based on age and sex for analysis. Pearson’s correlation test was done to establish a relation between age and volume of the gland and a p-value of <0.05 was considered as significant. Results: Our study included 137 patients (57 males, 80 females) with age ranging from 3 to 86 years. The study was divided into six age groups. Mean pituitary height, AP diameter, transverse diameter and volume of the gland were 6mm, 8.9mm, 12.3 mm, and 354.5 mm3 respectively. The gland observed a gradual increase in size up to the third decade and was more pronounced in the female population. A steady decline in the size of the gland was noted after 30 years for both populations. Conclusion: Good understanding of the normal size and shape of pituitary gland and its variation with age and gender is a must for every radiologist to compare with an abnormal increase in size.